A social systems approach to understanding the racial effect of the Section 44 counter-terror stop and search powers. Issue 4 (2nd November 2015) - Herron, Rachel
Abstract: In 2010, the European Court of Human Rights (ECtHR) endorsed long-standing claims of the potentially discriminatory effect of the suspicionless stop and search powers within s.44 of the Terrorism Act 2000. This paper applies principles of social systems theory to propose an explanation for the empirically evidenced racial effect of the s.44 police powers. Through observations regarding communicative barriers apparent between the law-making and policing subsystems, the paper argues that each subsystem's understanding of the expectations of the other, pertaining to the nature and use of the s.44 powers, contributed to their deployment in a way that diminished the effectiveness of the safeguards intended to guard against their misuse. Mismatched subsystem expectations meant that the powers were implemented by the police without the statutory protections, the operational self-restraint, or the type of intelligence-led judgment expected by the legislature, giving rise to misuse of the powers and, in particular, their deployment in line with race-based profiles.